2013
DOI: 10.1038/bmt.2013.192
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of high-dose melphalan and auto-SCT in patients with AL amyloidosis and cardiac involvement

Abstract: In Ig light chain (AL) amyloidosis, cardiac involvement is associated with worse prognosis and increased treatment-related complications. In this retrospective cohort study, we assessed survival, hematologic and cardiac responses to high-dose melphalan and auto-SCT (HDM/SCT) in patients with AL amyloidosis and cardiac involvement, stratified by cardiac biomarkers brain natriuretic peptide and Troponin I, analogous to the Mayo cardiac staging. Forty-seven patients underwent HDM/SCT based upon functional measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…As we utilize a low threshold for ICU transfers for transplant patients with cardiac arrhythmias, it may have contributed to the improved overall mortality and outcome. In the current study, HR was observed in 86% of the patients at 1-year post transplant with 23% CHR, comparable to the previous reports including Madan et al, 14 where a HR of 66% and CHR of 30% were reported in 187 cardiac amyloidosis patients, and Girnius et al, 22 where 27% CHR in 47 cardiac amyloidosis patients was reported in HDT-ASCT setting. However, as opposed to the recent data reported by the Mayo group, 23 HR before transplant (63%) or in the immediate post-transplant setting (80%) did not translate into improved OS or EFS in our study.…”
Section: Discussionsupporting
confidence: 80%
“…As we utilize a low threshold for ICU transfers for transplant patients with cardiac arrhythmias, it may have contributed to the improved overall mortality and outcome. In the current study, HR was observed in 86% of the patients at 1-year post transplant with 23% CHR, comparable to the previous reports including Madan et al, 14 where a HR of 66% and CHR of 30% were reported in 187 cardiac amyloidosis patients, and Girnius et al, 22 where 27% CHR in 47 cardiac amyloidosis patients was reported in HDT-ASCT setting. However, as opposed to the recent data reported by the Mayo group, 23 HR before transplant (63%) or in the immediate post-transplant setting (80%) did not translate into improved OS or EFS in our study.…”
Section: Discussionsupporting
confidence: 80%
“…We observed CR rates in the 30% to 40% range, similar to those previously reported by other groups. 2,15,16,36,37,41,42 TRM after HDM was very low with a single death. Because eligibility criteria for HDM at our institution are comparable to those of other centers, 15 our study is representative and corroborates the value of HDM as a treatment option for selected eligible patients at experienced centers, even in the era of novel agents.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose melphalan with autologous hematopoietic cell transplantation (auto-HCT) can provide deep hematological responses, reversal of amyloid-related organ dysfunction, and sustained disease control in a subset of fitter AL amyloidosis patients [2][3][4]. Despite its promise, treatment with this modality has so far been limited by high treatment-related mortality for many patients, owing to high morbidity from amyloid organ involvement [5,6]. Recent trends have shown improved outcomes of auto-HCT in experienced transplantation centers that adhere to careful patient selection [7].…”
Section: Introductionmentioning
confidence: 98%